2013
DOI: 10.1002/14651858.cd004074.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of umbilical cord clamping of term infants on maternal and neonatal outcomes

Abstract: A more liberal approach to delaying clamping of the umbilical cord in healthy term infants appears to be warranted, particularly in light of growing evidence that delayed cord clamping increases early haemoglobin concentrations and iron stores in infants. Delayed cord clamping is likely to be beneficial as long as access to treatment for jaundice requiring phototherapy is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
227
4
15

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(254 citation statements)
references
References 73 publications
8
227
4
15
Order By: Relevance
“…However, there is considerable variation between babies. A Cochrane review [15] of 15 trials including 3,911 women and term infant pairs showed no negative maternal effects of delayed cord clamping. Delayed cord clamping increased the newborn's hemoglobin at 12-24 h of age, as well as the risk of jaundice needing phototherapy, and reduced iron deficiency at 3-6 months of age.…”
Section: Cord Clamping and Cord Milkingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is considerable variation between babies. A Cochrane review [15] of 15 trials including 3,911 women and term infant pairs showed no negative maternal effects of delayed cord clamping. Delayed cord clamping increased the newborn's hemoglobin at 12-24 h of age, as well as the risk of jaundice needing phototherapy, and reduced iron deficiency at 3-6 months of age.…”
Section: Cord Clamping and Cord Milkingmentioning
confidence: 99%
“…Delayed cord clamping increased the newborn's hemoglobin at 12-24 h of age, as well as the risk of jaundice needing phototherapy, and reduced iron deficiency at 3-6 months of age. However, delayed cord clamping was defined differently in these studies - from 30 s to 1 or even 5 min after birth or until the cord stopped pulsating [15]. …”
Section: Cord Clamping and Cord Milkingmentioning
confidence: 99%
“…The timing of cord clamping (CC) as an active intervention during the third stage of labour is recognized as an important factor in influencing perinatal and maternal outcomes [1,2,3]. Several studies have investigated the timing of CC and its direct effects, describing the risks and benefits for both early and delayed CC (ECC and DCC) [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the timing of CC and its direct effects, describing the risks and benefits for both early and delayed CC (ECC and DCC) [1,2,3,4,5,6]. DCC has been shown to decrease the risk of anaemia, hypovolemia and respiratory distress syndrome [1,3,5,6], while the risk for hyperbilirubinemia is increased [1,2,3,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Para reducir la anemia en lactantes, se debería iniciar la suplementación con hierro, entre los dos a cuatro meses de edad, especialmente en los nacidos de madres anémicas, así como fomentar el clampaje tardío del cordón umbilical para mejorar los depósitos de hierro (21)(22) . Se debe realizar un seguimiento a los recién nacidos de madres anémicas, e incluir la evaluación de hemoglobina antes de los 6 meses de edad.…”
Section: Discussionunclassified